Increased radical scavenging activity of thymoquinone and L-ascorbic acid dual encapsulated in palmitoyl-chitosan nanoparticles in a human normal lung fibroblast, MRC-5 due to synergistic antioxidative effects - Othman, Nurhanisah; Md. Jamil, Siti Nurul Ain; Masarudin, Mas Jaffri; Mohd Jusoh, Ruqayyah Ainul Bashirah; Alamassi, Mohammed Numan (Royal Society of Chemistry, 2023)
Less effective antioxidant supplementation in combating free radicals is often related to the lack of the formulation of carriers. The antioxidant may be one of the most powerful substances but is marred by poor uptake by cells when the carrier degraded and dissolved too rapidly. Nanoparticle (NP) systems are promising in overcoming the problem since they provide high surface area to enhance encapsulation and release efficiency. With the right selection of material, NP carriers could function as constructive antioxidant cargos. Generally, NPs carry only one active ingredient; this study, however, utilized chitosan nanoparticles (CNPs) and hydrophobically modified palmitoyl-chitosan nanoparticles (PCNPs) that were dual encapsulated with antioxidants of different polarities, namely, hydrophobic thymoquinone (TQ) and hydrophilic L-ascorbic acid (LAA) to evaluate their combination effects in scavenging free radicals. The antioxidants followed zero-order release kinetics with a controlled release manner for about 48 h. The interaction effects between TQ and LAA loaded in the NP systems were determined by classical isobologram (CI) values. The CI values were derived by a diphenyl picrylhydrazyl (DPPH) assay, a radical scavenging activity assay. Combined TQ and LAA had CI values of less than one, with a lower value in the PCNP system than in the CNP system. This indicates that the interaction between those antioxidants showed higher synergistic effects in PCNPs, which enhanced the DPPH radical scavenging activities. The antioxidative potential of compound(s) encapsulated in the PCNP carrier was further experimented by a reactive oxygen species (ROS) assay on a human normal lung fibroblast cell line (MRC-5) as lung is one of the organs with high accumulation of free radicals. About 48 h post treatment, the dual-loaded TQ and LAA in PCNPs showed the lowest ROS level in comparison to single-loaded antioxidants and bare antioxidant delivery. The hydrogen peroxide (H2O2) radical scavenging was influenced by both the controlled release property of the PCNP system and the synergy between TQ and LAA. In short, dualloaded TQ and LAA in the hydrophobically modified PCNP had effectively depicted the capability of a single CS-based nanocarrier to hold more than one compound at a time to function as a potent radical scavenger.